Appropriate constraints for variational optimization of electronic density matrices and electron densities - Payne, Philip W. (1982)
Euler equations characteristic of the electronic reduced density matrix have previously been obtained by minimizing an energy functional subject to trace constraints 〈P(K)〉 = N, in which N is the number of particles. It is shown that these constraints are inadequate to exclude variations that violate N-representability conditions. However, a first-order reduced density matrix that does satisfy N-representability conditions is formulated as a functional of the orbital densities through use of angular momentum recoupling. Modified variational constraints are proposed.